Starch-based orodispersible film for diclofenac release (Brazilian Journal of Pharmaceutical Sciences, 2023)
The form of drug administration affects the success of treatment, since it can influence adherence of the patient to the therapy. The use of orodispersible films has emerged as a way to overcome some drawbacks of conventional methods of drug delivery, especially for patients experiencing difficulty in swallowing. These films are prepared using a matrix that incorporates the drug and contains other substances that confer the properties of the system. The present work describes the use of thermoplastic starch as a carrier for the model drug diclofenac, including film preparation and testing of its orodispersible potential. Preparation of the film employed a microwave oven to gelatinize and plasticize corn starch, with incorporation of the model drug, followed by solvent-casting. The samples were characterized using mechanical tests, analyses of water uptake and water content, and Fourier transform infrared spectroscopy. The results indicated that the film presented promising properties as an alternative system for oral drug administration, with good incorporation and distribution of the drug in the matrix. The material displayed satisfactory mechanical properties, which are crucial for this type of material, due to the need for oral administration and handling before use.